A novel MAC proposal for critical and emergency communications in Industrial Wireless Sensor Networks. (November 2018) - Raza, Mohsin; Le-minh, Hoa; Aslam, Nauman; Hussain, Sajjad
Abstract: In this paper, three MAC protocols, EE-MAC, CF-MAC and OD-MAC, are proposed. EE-MAC incorporates emergency communication and allows immediate channel access for emergency traffic. CF-MAC compensates regulatory and open-loop control traffic and introduces a prioritized access for high priority nodes. It also allows nodes with critical data to reserve communication slots using control channel. Whereas OD-MAC presents a deadline based dynamic scheduler which ensures timely delivery of time-critical information. The paper presents mathematical modelling of the proposed protocols. For evaluation purposes, the performance of the proposed protocols is compared to IEEE 802.15.4e LLDN. The results show that the proposed protocols offer up to 92% reduction in delay in emergency communications at the cost of 5% to 15% increase in delay of time-insensitive data. A 60% and 85% reduction was observed in the channel access delay for regulatory and open-loop control traffic respectively along with notable improvements in communications reliability.